2023
DOI: 10.3389/fbioe.2023.1204737
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pro-inflammatory cytokine priming and storage temperature of the mesenchymal stromal cell (MSC) secretome on equine articular chondrocytes

Manon Jammes,
Romain Contentin,
Fabrice Audigié
et al.

Abstract: Context: Osteoarthritis (OA) is an invalidating articular disease characterized by cartilage degradation and inflammatory events. In horses, OA is associated with up to 60% of lameness and leads to reduced animal welfare along with extensive economic losses; currently, there are no curative therapies to treat OA. The mesenchymal stromal cell (MSC) secretome exhibits anti-inflammatory properties, making it an attractive candidate for improving the management of OA. In this study, we determined the best storage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 74 publications
(107 reference statements)
1
6
0
Order By: Relevance
“…IL1β- and TNFα-exos tended to induce a stronger increase in type I and IIB collagens accumulation than naive- and IFNγ-exos, while also increasing Htra1 levels. This observation suggests the diversity of the molecular pathways associated with the pro-inflammatory stimulation of MSCs, confirming our previous results on CMs derived from primed BM-MSCs [ 24 ]. Because a single cytokine does not recreate the whole pro-inflammatory environment that occurs in OA joints, associating several immunomodulatory markers could potentialize their priming potential and improve MSC-exos therapeutic capacities.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…IL1β- and TNFα-exos tended to induce a stronger increase in type I and IIB collagens accumulation than naive- and IFNγ-exos, while also increasing Htra1 levels. This observation suggests the diversity of the molecular pathways associated with the pro-inflammatory stimulation of MSCs, confirming our previous results on CMs derived from primed BM-MSCs [ 24 ]. Because a single cytokine does not recreate the whole pro-inflammatory environment that occurs in OA joints, associating several immunomodulatory markers could potentialize their priming potential and improve MSC-exos therapeutic capacities.…”
Section: Discussionsupporting
confidence: 91%
“…However, the therapeutic potential of exosomes derived from naive BM-MSCs can be enhanced through various stimulation techniques, including the use of pro-inflammatory cytokines. In a previous study, we demonstrated that the priming of BM-MSCs with equine IL-1β, TNF-α, or IFN-γ can modulate the effects mediated by their secretome on cartilaginous organoids [ 24 ]. Here, we aimed to investigate whether exosomes isolated from primed BM-MSCs can also mediate similar effects.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations